THE SOCIAL STATUS OF PERSONS WITH DISABILITIES IN BOSNIA AND HERZEGOVINA - Elezovic, Stefan (Politeia, 2025)
Duško Trninić: Life Stories from the Social Margins: A Contribution to the Sociology of Disability (Association for Philosophy and Social Thought, Banja Luka, 2024)